Cost‐Effectiveness of Surgery Versus Organ Preservation in Advanced Laryngeal Cancer. (10th August 2020) - Beck, Ann‐Jean C. C.; van Harten, Wim H.; van den Brekel, Michiel W. M.; Navran, Arash; Retèl, Valesca P.
Abstract : Objective: Treatment decision‐making for patients with laryngeal cancer consists of a complex trade‐off between survival and quality of life. For decision makers on coverage and guidelines, costs come in addition to this equation. Our aim was to perform a cost‐effectiveness analysis of surgery (laryngectomy with or without radiotherapy) versus organ preservation (OP: radiotherapy, chemo‐ and/or bioradiation) in advanced laryngeal cancer patients from a healthcare perspective. Methods: A cost‐effectiveness analysis was conducted using a Markov model. For each modality, data on survival and quality‐adjusted life years (QALYs) were sourced from relevant articles in agreement with experts, and national benchmark cost prices were included regarding treatment, follow‐up, adverse events, and rehabilitation. Results: Total QALYs of the surgical approach (6.59) were substantially higher compared to the OP approach (5.44). Total lifetime costs were higher for the surgical approach compared to the OP approach, namely €95, 881 versus €47, 233. The surgical approach was therefore more effective and more costly compared to OP, resulting in an incremental cost‐effectiveness ratio of €42, 383/QALY. Conclusion: Based on current literature, surgical treatment was cost‐effective compared to OP in advanced laryngeal cancer within most willingness‐to‐pay thresholds. The study provides information on the survival adjusted for quality of life in combination with costs of two different approaches for advanced laryngeal cancer, relevant for patients, physicians, and policy makers. As financial toxicity is a relevant aspect in this population, collection of real‐world data on country‐specific costs and utilities is strongly recommended to enable further generalization. Level of Evidence: N/A. Laryngoscope, 131:E509–E517, 2021